Risk of Delayed Lymph Node Metastasis in Clinically N0 Esthesioneuroblastoma - Peacock, Justin G.; Harmsen, William S.; Link, Michael J.; Van Gompel, Jamie J.; Giannini, Caterina; Olsen, Kerry D.; Garces, Yolanda I.; Neben Wittich, Michelle A.; Ma, Daniel J.; Park, Sean S.; Foote, Robert L. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objective To determine both the rate of delayed cervical lymph node metastasis in patients with esthesioneuroblastoma (ENB) and a clinically N0 untreated neck and the effectiveness of salvage treatment.Design Retrospective review.Setting Tertiary academic medical center.Participants All patients from January 1, 1965, to December 31, 2010, who received definitive treatment for ENB.Main Outcome Measures The study involved 52 patients: 27 (52%) patients underwent surgery and adjuvant radiotherapy (SART) to the primary site only and 25 (48%) underwent surgery alone (SA) as treatment of the primary site, without elective neck dissection.Results Median follow-up for the SART group was 10 years versus 15.7 years for the SA group. The 10-year delayed cervical lymph node metastasis estimate is 41%. With median follow-up of 47 months after salvage treatment, the 4-year cervical lymph node recurrence-free survival estimate is 70%; the 5-year overall survival estimate is 39%.Conclusions Delayed cervical lymph node metastases are common, indolent, and salvaged effectively in most patients. We propose that patients with ENB and clinically N0 cervical lymph nodes may choose to forego elective neck dissection or elective neck radiotherapy in favor of neck observation within their initial treatment.
Keywords: cervical lymph node metastasis; esthesioneuroblastoma; radiotherapy; surgery